Pengaruh Debt To Equity Ratio, Profitabilitas, Kualitas Auditor, Pergantian Auditor, Opini Auditor Dan Kepemilikan Publik Terhadap Ketepatan Waktu Pelaporan Keuangan (Pada Perusahaan Consumer Non Cyclical Yang Terdaftar Di Bei Periode 2019-2022) - Istikharoh Istikharoh; Nafi Inayati Zahro; Zaenal Afifi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to determine the effect of debt to equity ratio, profitability, auditor quality, auditor turnover, auditor opinion and public ownership on the timeliness of financial reporting of consumer companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study were 54 companies in the consumer sector listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling and a total 0f 84 samples were obtained. The analytical method used is multiple linear regression analysis using statistical test tools Software Statistical Product and Service (SPSS) 21. The results of this research show that the debt to equity ratio has a negative effect on the timeliness of financial reporting, profitability has a positive effect on the timeliness of financial reporting, auditor quality has a negative effect on the timeliness of financial repoting, changing auditors has a negative effect on the timeliness of financial reporting, auditor opinion has a positive effect on the timeliness of financial reporting, and public ownership has a positive effect on the timeliness of financial reporting.